INCREASED SERUM NITRITE AND NITRATE LEVELS IN AMPHOTERICIN-B ADMINISTERED ALBINO RATS - C, Ashoka Kumar (Innoriginal: International Journal of Sciences, 2015)
Amphotericin B (Amp-B) usefulness is associated with a number of toxic cellular effects. We investigated the in-vivo effects of Amp-B on the nitrite (NO2-) and nitrate (NO3-) levels in the serum of rats administered with 0.5 or 1.5 mg/kg/wt of Amp-B over 4 or 10 weeks (i.v, weekly doses). The rat serum NO2-/NO3- levels appeared to be enhanced in the Amp-B administered rats compared to the untreated control group of rats and the changes observed were found to be in a dose and time – dependent manner. Based on the results, it is reported that Amp-B by way of enhancing the production of nitric oxide (NO) may contribute for more production of NO end products like NO2-/NO3- and these intern may be helpful in reducing the fungal affects, since Amp-B is the drug of choice used against fungal infections in clinical trails